Heat transfer through loess cover layers above thermally active coal gangue zones for vegetation root-zone protection: Large-scale experiments and numerical simulation - Ang Li; Chengkun Song; Wenzhuo Qiu; Jing Fang; Min Li; Bole Yi (Journal of Environmental Chemical Engineering, 2026)

A source-reduction process via mechanical activation assisted K2SO4 roasting and closed-loop recycling of potassium salt for efficient lithium extraction from lepidolite - Dong-qi Song; Shu-hao Dong; Long-long Zhou; Zi-ang Si; Shuai-bo Geng; Huan Li; Hui Guo (Chemical Engineering Journal, 2026)

Enhancing power-to-hydrogen efficiency: A streamline-shaped flow channel design for alkaline water electrolyzers verified using a microfluidic experimental platform - Xiudong Duan; Ziyu Liu; Ang Lu; Jiachang Wan; Fan Chen; Desheng Li; Xiaomeng Ai; Chaolong Song; Jiakun Fang (Chemical Engineering Journal, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

A sensory-calibrated electronic nose method for odor intensity quantification and grade identification in refrigerators - Shiwen Cheng; Li’ang Yin; Xiao Ye; Xiaozheng Liu; Yumei Qin; Yaqing Song; Suyun Zhang; Tengfei Yu; Chonghui Zhang; Shiyi Tian (Food Research International, 2026)

Research on Shear Creep-Impact Mechanical Model of Anchored Jointed Rock Masses with Combined Macro–Meso Parameters Under Constant Normal Stiffness Boundary Conditions - Jianhua Zhou; Yang Song; Heping Wang; Jingjing Duan; Wan Li; Ang Li (Rock Mechanics and Rock Engineering, 2026)

Designing hard-soft carbon composite anodes via a normalized pore volume-mass matching strategy for high-performance sodium storage - Xiaoqi Yu; Xiaoyu Xu; Hanyu Wei; Xiaofeng Zhang; Haiyan Liu; Chengwei Fan; Ang Li; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2026)

Contrasting responses to environmental stresses for macroinvertebrates and benthic algae in subtropic Qinhuai rivers - Lei Han; Ming Chen; Song Bai; Ang Hu; Peixuan Zhang; Beryl Ochieng; Yifan Cui; Jinfu Liu; Shaojuan Du; Hao Wu; Xiefa Song; Kang Song; et al. (Journal of Hydrology, 2026)

Characteristics and drivers of net ecosystem CO2 exchange in the Badain Jaran Desert - Ping Yang; Hang Zhao; Jinqiao Liu; Qingfan Song; Zhenmin Niu; Nai’ang Wang (Theoretical and Applied Climatology, 2026)

CFD Numerical Simulation Study on Hydrogen Fuel Combustion and Emission Characteristics of Marine Two-Stroke Low-Speed Engines - Zhizheng Wang; Hao Guo; Ang Sun; Song Zhou; Jialu Song; Yi Chai; Yue Chen (Journal of Marine Science and Engineering, 2026)
To meet the global climate change challenge and the International Maritime Organization’s (IMO) greenhouse gas emission reduction strategy, and promote the shipping industry’s transition to clean energy, this study focuses on the 6S35 2-stroke marine low-speed engine to explore hydrogen fuel combustion and emissions in the cylinder. A detailed chemical reaction kinetics model is constructed on the CONVERGE platform, coupling 42 components and 168 elementary reactions, integrating the SAGE combustion model with the extended Zeldovich NOx mechanism for refined numerical simulation of hydrogen combustion. Model validation shows the cylinder pressure peak simulation error is within 5%. Research results indicate hydrogen fuel has significant premixed combustion characteristics with a violent and concentrated heat release. Under simulation, the cylinder explosion pressure reaches about 28 MPa, and the max combustion temperature nears 3000 K, far exceeding traditional diesel engines. In terms of emissions, hydrogen’s carbon-free characteristic keeps CO2 and CO emissions at extremely low levels (concentrations of approximately 0.02 and 0.085, respectively); whereas NOx emissions exhibit strong “high temperature dependence” and “expansion cooling effect,” with peak concentrations approaching 0.00042. This numerical model can effectively predict the combustion performance of hydrogen fuel, potentially providing a reference for optimizing fuel injection strategies and combustion chamber design to achieve efficient and clean combustion, and offering a theoretical basis for the development and commercial application of marine hydrogen fuel engines.

Characterization and bifidogenic effects of a low-molecular weight polysaccharide isolated from a Chinese herb, Polygonatum kingianum Coll. et Hemsl (Huangjing) rhizome - Xiao-Hui Yuan; Ting-Ting Tu; Yu-Heng Mao; Yan-Chun Wang; Meng-Qi Huang; Lei- Wang; You Luo; Chun-Xiao Wang; Shu-Yi Qiu; Bin- Deng; Ang-Xin Song (Carbohydrate Polymers, 2026)

Diffusion mechanism of shield-synchronous grouting slurry and parameter optimization in water-rich fine sand formations - Yang Song; Ang Li; Zhixin Li; Xin Wang; Hao Li (Transportation Geotechnics, 2026)

Isolation, characterization, and anti-neuroinflammatory activity of sesquiterpenoids from Pogostemon esquirolii - Yebi Qin; Xinyan Shao; Yinzheng Xie; Hailin Lu; Kaien Chen; Xi Zheng; Guodong Chen; Lishe Gan; Song Ang; Dongli Li (Phytochemistry, 2026)

Synergistic 3d-5d orbital interactions on oxygen vacancy-rich Pt/TiO2 for enhanced photothermal catalytic oxidation of propylene - Xiaoxiao Zhu; Weidong Yuan; Siyi Song; Tong Chen; Wenjun Xiong; Sibo Wang; Jinpeng Hu; Rui Liu; Zhu Luo; Jinlong Wang; Ang Gao; Yanbing Guo (Chemical Engineering Journal, 2026)

Boosting the plateau capacity via phosphoric acid cross-linking strategy for phenolic resin-based hard carbon - Xiaoqi Yu; Xiaoyu Xu; Hanyu Wei; Haiyan Liu; Ang Li; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2025)

Acetylated glucomannan-CNT scaffolds with dual-drug release promote hiPSCs-driven cortical regeneration by suppressing inflammation and anoikis - Yue Gao; Wenxi Li; Wanting Lu; Fuqiang Tang; Xian Xiao; Yinggang Li; Jiaxing Huang; Zhiqi Liang; Yuqing Wu; Yanwen Li; Qingjian Zou; Liangxue Lai; et al. (Carbohydrate Polymers, 2025)

Cyanoalanine Synthase encoding gene SlCAS1 regulates tomato fruit ripening by modulating pigment metabolism and ethylene biosynthesis - Song-Li Han; Yu-Qi Zhao; Li-Xia Li; Pedro Garcia-Caparros; Yan-Hong Li; Zhen Wang; Yi-Ang Feng; Kang-Di Hu; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2025)

A laser with instability reaching 4 × 10 - 17 based on a 10-cm-long silicon cavity at sub-5-K temperatures - Zhi-Ang Chen; Hao-Ran Zeng; Wen-Wei Wang; Han Zhang; Run-Qi Lei; Jian-Zhang Li; Cai-Yin Pang; She-Song Huang; Xibo Zhang (Science Bulletin, 2025)

Quantifying graphitic curvature and engineering closed pores in phenolic resin hard carbons for enhanced plateau capacity in sodium-ion batteries - Xiaotian Li; Jiapeng Zhang; Renlu Yuan; Boyang Zhao; Chuang Qiu; Dengke Wang; Man Yuan; Ang Li; Haiyan Liu; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2025)

Anti-aging effect of tea and its phytochemicals - Huijun Liang; Mei Qu; Song Ang; Dongli Li; Chengwei He (Food Research International, 2025)

Sulfur-bonded hard carbon with enhanced interfacial and bulk kinetics for potassium-ion hybrid capacitors - Chuang Qiu; Anuj Kumar; Mohammad Tabish; Xinzhuo Mai; Liewen Guo; Ying Zhao; Yibo Zhu; Ang Li; Ghulam Yasin; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2025)

Multiplex quantitative PCR assay for porcine circoviruses 2 and 3 and its application for measuring infection rates at different stages of pig production - Zhen Li; Shuaiyin Guan; Jiaying Zhao; Yuhuan Chen; Yang Han; Ang Tian; Saisai Zhou; Huanchun Chen; Yunfeng Song (Archives of Virology, 2025)

Characterization of two pectic polysaccharides from Rosa roxburghii Tratt fruit and their protection on Bifidobacterium against antibiotic damage - Ting-Ting Tu; Xiao-Hui Yuan; Yu-Heng Mao; Yan-Chun Wang; Zheng-Hao Chen; Lei Wang; You Luo; Chun-Xiao Wang; Shu-Yi Qiu; Ang-Xin Song (Food Bioscience, 2025)

Photothermal halloysite nanotube hybrids with CoO/carbon layers for enhanced pollutant degradation and solar-powered water purification - Yifang Zhang; Hongyao Zhao; Jiayi Zhou; Yanyun Wang; Yangping Zhang; Jialing Shen; Danhong Shang; Feng Zeng; Jianming Pan; Yiyan Song; Fu Yang; Edison Huixiang Ang (Desalination, 2025)

Spatial configuration engineering of phenolic resins to tune the closed pores of hard carbon for enhanced plateau-capacity sodium storage - Liewen Guo; Chuang Qiu; Haiyan Liu; Renlu Yuan; Xiaotian Li; Xin Li; Kairan Li; Wanxiong Zhu; Mohammad Tabish; Xuewei Liu; Ang Li; Xiaohong Chen; et al. (Chemical Engineering Journal, 2025)

High content of single-atomic sulfur in nano carbon spheres boosting potassium storage performance - Bin Cao; Zirong Guo; Huan Liu; Yu Ma; Wei Zhao; Yiheng Yang; Ang Li; Huaihe Song; Yaxiong Yang; Zhenglong Li; Wubin Du (Chemical Engineering Journal, 2025)

High-Voltage aqueous supercapacitors based on l-lysine pH Self-Buffering Coating-modified carbon cloth electrode - Ang Xu; Jie Gao; Huan Li; Xiyu Song; Bo Xu; Ying Liu; Yuanyuan Yu; Ping Wang; Qiang Wang; Man Zhou (Chemical Engineering Journal, 2025)

Generation and resource potential of waste PV modules considering technological iteration: A case study in China - Zishuo Wang; Bo Li; Xiaolong Song; Xuning Zhuang; Wenjie Wu; Ang Li (Environmental Impact Assessment Review, 2025)

Methane emissions from the riverine sandy wetlands on the Mongolia Plateau - Ang Li; Zun-Lan Luo; Katerina Machacova; Song Zhao; Jin-Chao Feng; Xing-Guo Han; Zhi-Ping Wang (Environmental Monitoring and Assessment, 2024)

Janus-structured colorimetric and fluorescent nanocomposites with highly luminescent retention to enhance point-of-care diagnosis - Xuan-ang Shen; Xirui Chen; Haoxiang Zhou; Song Chen; Jinyu Wu; Xiangmin Li; Xiaolin Huang; Yonghua Xiong (Chemical Engineering Journal, 2024)

Research on fine modeling of dispersion fuel plate based on lattice method - Yuqing Chen; Pengfei Liu; Song Li; Lei Lou; Ang Li (Annals of Nuclear Energy, 2024)

Sustainable reprocessing of lithium iron phosphate batteries: A recovery approach using liquid-phase method at reduced temperature - Tingyan Ren; Bolin Zou; Bin Cai; Tong Liang; Junhao Chen; Rui Huang; Dahai Yang; Hongfa Xiang; Edison Huixiang Ang; Xiaohui Song (Waste Management, 2024)

Elucidating the unexpected importance of intermediate-volatility organic compounds (IVOCs) from refueling procedure - Xinping Yang; Kai Song; Song Guo; Yunjing Wang; Junfang Wang; Di Peng; Yi Wen; Ang Li; Baoming Fan; Sihua Lu; Yan Ding (Journal of Hazardous Materials, 2024)

Low-temperature hydrogen production from waste polyethylene by nonthermal plasma (NTP)-assisted catalytic pyrolysis using NiCeOx/β catalyst - Jiaxing Song; Jiabao lv; Yuhan Pan; Jingyu Wang; Jun Wang; Ang Cao; Angjian Wu; Paul T. Williams; Qunxing Huang (Chemical Engineering Journal, 2024)

Quantitative prediction of surrounding rock deformation via an energy-based damage model combining with microseismic monitoring - Dingran Song; Yi Liu; Feng Dai; Ruochen Jiang; Ang Li (Tunnelling and Underground Space Technology, 2024)

Generation estimation and critical metals quantity assessment of retired mobile phones in Japan - Ang Li; Bo Li; Ge Yang; Kronnaphat Khumvongsa; Jingjin Pan; Xiaolong Song; Xuyang Lei; Suxia Hou; Dong Yang; Bin Lu (Journal of Cleaner Production, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

High-density lipoprotein regulates angiogenesis by affecting autophagy via miRNA-181a-5p - Bi-Ang Kang; Hua-Ming Li; Ya-Ting Chen; Meng-Jie Deng; Yan Li; Yue-Ming Peng; Jian-Jun Gao; Zhi-Wei Mo; Jia-Guo Zhou; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2024)

Patterns and drivers of atmospheric inorganic nitrogen deposition in Northeast Asia - Abubakari Said Mgelwa; Feifei Zhu; Dan Huang; Linlin Song; Yingying Wang; Geshere Abdisa Gurmesa; Ang Wang; Miao Liu; Shaonan Huang; Qingyan Qiu; Hiroyuki Sase; Weixing Zhu; et al. (Journal of Environmental Management, 2024)

On-demand detachable adhesive hydrogel based on dual dynamic covalent cross-linked with NIR/pH dual-responsive properties for diabetic wound healing - Kaize Su; Duanyu Deng; Xiaoxian Wu; Yumu Song; Ying Sun; Xu Wang; Zhen Zhang; Jinxuan Li; Zhenping Yan; Xiangcun Shang; Chen Li; Kun Zhang; et al. (Chemical Engineering Journal, 2024)

Hirsutinolide-type sesquiterpenoids with anti-prostate cancer activity from Cyanthillium cinereum - Song Ang; Chun Liu; Peng Hong; Lei Yang; Gui'e Hu; Xi Zheng; Jingwei Jin; Rihui Wu; Wing-Leung Wong; Kun Zhang; Lishe Gan; Dongli Li (Phytochemistry, 2023)

Particulate organic emissions from incense-burning smoke: Chemical compositions and emission characteristics - Kai Song; Rongzhi Tang; Ang Li; Zichao Wan; Yuan Zhang; Yuanzheng Gong; Daqi Lv; Sihua Lu; Yu Tan; Shuyuan Yan; Shichao Yan; Jingshun Zhang; et al. (Science of The Total Environment, 2023)

Reduced nitrogen fertilization from pre-flowering to pre-veraison alters phenolic profiles of Vitis vinifera L. Cv. Cabernet Gernischt wine of Yantai, China - Jianqiang Song; Ang Zhang; Fei Gao; Mingqing Li; Xianhua Zhao; Jie Zhang; Genjie Wang; Yuping Hou; Shiwei Cheng; Huige Qu; Shili Ruan; Jiming Li (Food Research International, 2023)

Maternal exposure to 4-vinylcyclohexene diepoxide during pregnancy induces subfertility and birth defects of offspring in mice - Wei Song; Ang Li; Qian-Qian Sha; Shao-Yuan Liu; Yong Zhou; Chang-Yin Zhou; Xue Zhang; Xiao-Zhen Li; Jia-Xin Jiang; Fei Li; Chao Li; Heide Schatten; et al. (Science of The Total Environment, 2023)

Characterization and shifting of microbial community to denitrification for anaerobic sulfamethoxazole biodegradation with different electron acceptors - Xiaoli Su; Feiyun Sun; Jianjun Zhang; Dingyu Xing; Xiaoying Li; Zi Song; Liang Feng; Zhichao Huang; Ang Li (Journal of Cleaner Production, 2023)

Intrinsic ionic confinement dynamic engineering of ionomers with low dielectric-k, high healing and stretchability for electronic device reconfiguration - Jingwen Wang; Yapeng Zheng; Wei Ren; Edison Huixiang Ang; Lei Song; Jixin Zhu; Yuan Hu (Chemical Engineering Journal, 2023)

A feasibility study on the use of hydrophobic eutectic solvents as pseudo-stationary phases in capillary electrophoresis for chiral separations - Ang Li; Song Xue; Yu Xu; Sihui Ding; Di Wen; Qi Zhang (Analytica Chimica Acta, 2023)

Generation estimation and material flow analysis of retired mobile phones in China - Ang Li; Bo Li; Bin Lu; Dong Yang; Suxia Hou; Xiaolong Song (Environmental Science and Pollution Research, 2022)

Canonical transformation for multivariate mixed model association analyses - Li’ang Yang; Ying Zhang; Yuxin Song; Hengyu Zhang; Runqing Yang (Theoretical and Applied Genetics, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Improvement of laccase activity by silencing PacC in Ganoderma lucidum - Jing Zhu; Shuqi Song; Lindan Lian; Liang Shi; Ang Ren; Mingwen Zhao (World Journal of Microbiology and Biotechnology, 2022)

Research on Wetting Deformation Model of Coarse-Grained Materials of Earth-rock Dam - Hongyang Zhang; Pengju Han; Qin He; Yadong Sun; Ziyi Song; Zelin Ding; Ang Niu (Arabian Journal of Geosciences, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Regulation of glutamine synthetase activity by transcriptional and posttranslational modifications negatively influences ganoderic acid biosynthesis in Ganoderma lucidum - Jing Zhu; Shuqi Song; Zehua Sun; Lingdan Lian; Liang Shi; Ang Ren; Mingwen Zhao (Environmental Microbiology, 2021)
Summary Glutamine synthetase (GS), a central nitrogen metabolic enzyme, plays important roles in the nitrogen regulation network and secondary metabolism in fungi. However, the mechanisms by which external nitrogen sources regulate fungal GS activity have not been determined. Here, we found that GS activity was inhibited under nitrate conditions in Ganoderma lucidum . By constructing gs ‐silenced strains and adding 1 mM GS inhibitor to inhibit GS activity, we found that a decrease in GS activity led to a decrease in ganoderic acid biosynthesis. The transcription of gs increased approximately five fold under nitrate conditions compared with that under ammonia. Electrophoretic mobility shift and yeast one‐hybrid assay showed that gs was transcriptionally regulated by AreA. Although both gs expression and GS protein content increased under nitrate conditions, the GS activity still decreased. Treatment of recombinant GS with SIN‐1 (protein nitration donor) resulted in a strengthened nitration accompanied by a 71% decrease in recombinant GS activity. Furthermore, intracellular GS could be nitrated from mycelia cultivated under nitrate conditions. These results indicated that GS activity could be inhibited by NO‐mediated protein nitration. Our findings provide the first insight into the role of transcriptional and posttranslational regulation of GS activity in regulating secondary metabolism in fungi.

Dual functions of AreA, a GATA transcription factor, on influencing ganoderic acid biosynthesis in Ganoderma lucidum - Jing Zhu; Zehua Sun; Dengke Shi; Shuqi Song; Lingdan Lian; Liang Shi; Ang Ren; Hanshou Yu; Mingwen Zhao (Environmental Microbiology, 2019)
Summary Nitrogen metabolism repression (NMR) has been well studied in filamentous fungi, but the molecular mechanism of its effects on fungal secondary metabolism has been generally unexplored. Ganoderic acid (GA) biosynthesis in Ganoderma lucidum differs between ammonia and nitrate nitrogen sources. To explain the functions of NMR in secondary metabolism, AreA, which is a core transcription factor of NMR, was characterized in G . lucidum . The transcription level of AreA was dramatically increased (approximately 4.5‐folds), with the nitrate as the sole nitrogen source, compared with that with ammonia as the source. In addition, the expression of related genes involved in NMR was changed (upregulated of MeaB and downregulated of Nmr and GlnA ) when AreA was knockdown. Yeast one‐hybrid and electrophoretic mobility shift assay results showed that AreA could directly bind to the promoter of fps (encoding farnesyl‐diphosphate synthase) to activate its expression. However, GA biosynthesis was increased (27% in the ammonia source and 77% in the nitrate source) in AreAi mutant strains versus that in control strains. These results showed that another important factor must participate in regulating GA biosynthesis other than the direct activation of AreA. Furthermore, we found that the content of nitric oxide (NO) was increased approximately 2.7‐folds in the nitrate source compared with that in the ammonia. By adding the NO donor (SNP) or scavenger (cPTIO) and using NR ‐silenced or NR ‐overexpressed strains, we found that there was a negative correlation between the NO contents and GA biosynthesis. NO generated by nitrate reductase (NR) during the nitrogen utilization burst and could negatively influence GA biosynthesis. As a global transcription factor, AreA could also regulate the expression of NR . Our studies provide novel insight into the dual functions of AreA in GA biosynthesis during nitrogen assimilation.

Impact of agricultural land use on aquatic insect assemblages in the Garonne river catchment (SW France) - Mi-Young Song; Fabien Leprieur; Alain Thomas; Sithan Lek-Ang; Tae-Soo Chon; Sovan Lek (Aquatic Ecology, 2009)

Genetic Variation in Hippophae rhamnoides ssp. sinensis (Elaeagnaceae) Revealed by RAPD Markers - Kun Sun; Wen Chen; Ruijun Ma; Xuelin Chen; Ang Li; Song Ge (Biochemical Genetics, 2006)

Note: A Preliminary Study on Conservation Genetics of an Endangered Orchid (Paphiopedilum micranthum) from Southwestern China - Ang Li; Yi-bo Luo; Song Ge (Biochemical Genetics, 2002)